2005
DOI: 10.4064/ap85-2-2
|View full text |Cite
|
Sign up to set email alerts
|

Criteria for univalence, starlikeness and convexity

Abstract: Abstract. Let A denote the class of all normalized analytic functions f (f (0) = 0 = f (0) − 1) in the open unit disc ∆. For 0 < λ ≤ 1, defineRecently, the problem of finding the starlikeness of these classes has been considered by Obradović and Ponnusamy, and later by Obradović et al. In this paper, the authors consider the problem of finding the order of starlikeness and of convexity of U (λ) and P(2λ), respectively. In particular, for f ∈ A with f (0) = 0, we find conditions on λ, β * (λ) and β(λ) so that U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Theorem 2.3 implies that the conjecture proposed in [5] is not true. Indeed, if it were, even for a single λ with 0 < λ ≤ 1, then for each fixed r < 1 we would have…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Theorem 2.3 implies that the conjecture proposed in [5] is not true. Indeed, if it were, even for a single λ with 0 < λ ≤ 1, then for each fixed r < 1 we would have…”
mentioning
confidence: 87%
“…The properties of functions in U (λ) and U 0 (λ) have been studied in detail in the literature (see [2]- [5]). Recently, Ponnusamy and Vasundhra [5] proposed the conjecture that f ∈ U 0 (λ) is convex at least when 0 < λ ≤ 3 − 2 √ 2. In [6], Vasundhra also obtained a lower bound for the radius of convexity of the families U (λ) and U 0 (λ).…”
mentioning
confidence: 99%
“…The class U{ 1) ξ U together with its various generalizations and subclasses have been discussed by M. Obradovic and S. Ponnusamy [9] and later by a number of authors (see [10,11,15]). In fact, Krzyz [6] has shown that function in U{λ) admits a Q-quasiconformal extension to the whole complex plane with Q = --γ whenever 0 < Λ < 1.…”
Section: Convolution Theoremsmentioning
confidence: 99%
“…then the Hadamard product or convolution, denoted by / * g. is defined bv"X il*fl)(z) = Σ ":'>•>'" 11=0and that /»9 ξ W. Next, we consider the class U{\) (0 < λ < 1 ) which is defined as follows:U(A) = |/ e A : j(ypy) /'( = ) -lj < A. ; € ΔThe class U{ 1) ξ U together with its various generalizations and subclasses have been discussed by M. Obradovic and S. Ponnusamy ¡9! and later by a number of authors (see[10,11,15]). In fact.Krzyz ;6] has shown that function in U( A) admits a Q-quasiconformal extension to the whole complex plane with Q = --γ whenever 0 < A < 1.…”
mentioning
confidence: 99%